An Equilibrium Search Model with Coworker Discrimination - Sasaki, Masaru (Journal of Labor Economics, 1999)
This article analyzes the effect of coworker discrimination on wage and unemployment differentials between males and females using a search model. An increase in female participation drives up the wage offer to female workers and raises female employment. Moreover, an increase in the degree of discrimination by males results in gains to them in terms of higher wages and lower unemployment but results in losses to females in terms of lower wages and higher unemployment. The benefit to males provides an explanation for the persistence of discrimination.